The effect of Noggin supplementation in Matrigel nanofiber‐based cell culture system for derivation of neural‐like cells from human endometrial‐derived stromal cells. Issue 1 (27th January 2014) - Tavakol, Shima; Modarres Mousavi, Sayed Mostafa; Massumi, Mohammad; Amani, Amir; Rezayat, Seyed Mahdi; Ai, Jafar
Abstract A very important obstacle in axonal regeneration after spinal cord injury is astroglial scaring. Noggin as bone morphogenic protein inhibitor plays a critical role in decreasing GFAP+ cells and reducing the number of astrocytes in the site of injury. Human endometrial‐derived stromal cells (hEnSCs) were isolated and cultured in two different neural inductive mediums consisting of neural progenitor maintenance medium (NPMM)/BDNF or NPMM/BDNF/Noggin in Matrigel 3D cell culture. Neural expression markers were investigated at the mRNA and protein level by real‐time PCR and immunocytochemistry, respectively. The results showed that Noggin supplementation was able to increase the expression of Nestin, Tuj‐1, and NF, whereas the expressions of GFAP, Bcl2, and Olig2 were decreased. In addition, DAPI staining demonstrated that lighter blue chromatin agreed with our observation of lower level of Bcl2 expression in the Noggin protocol in which over‐expression of Bcl2 gene did not induce higher neurogenesis in poor Noggin medium. Our findings clearly demonstrated the neural differentiation potential of hEnSC in Matrigel and also Noggin supplementation was able to inhibit astrocyte formation. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 1–7, 2015.